Memanfaatkan Media dalam Menghadapi Degradasi Kearifan Lokal Budaya Melayu di Indonesia: (Studi Kontestasi Penyampaian Pesan Budaya Melalui Media Perkawinan Melayu Deli) - Datuk Imam Marzuki (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This research is a historical research method, it is based on efforts to describe past events. This research also uses library-research (library research) trying to obtain complete information regarding the research topic, directing data issues and analysis sourced from library literature. The results of the research show that: First, there is a decline in the meaning of the idea of ​​function contained in rhymes and dances. The message is not conveyed well, because the function of rhymes and dances has shifted from conveying symbolic messages to just being for entertainment. Likewise, the procession is complicated, long, and the additional costs are one of the reasons the Deli Malay community is starting to stop using this culture. In the past, rhymes that were advice in nature were sometimes made humorous, this shifted the sacred nature of rhymes. The openness of the Deli Malay community has adjusted to market tastes.